Identifikasi dan Penilaian Fungsi Pohon Jalanan di Kabupaten Garut dan Sekitarnya - Kartikasari; Nasrullah, Nizar; Budiarti, Tati (Jurnal Lanskap Indonesia, 2025)
The street is an important city attribute that can reveal the existence of other city attributes that have meaning. Vegetation as one of the elements of the street or more precisely the green street can present a touch of life and beauty through its diversity of forms, and trees are a form of vegetation that is easily recognized because of their size. On the other side, Kabupaten Garut is a developing area that is building and repairing city infrastructure, especially street infrastructure. Identification and analysis of the function of street trees in Kabupaten Garut and its surrounding areas are necessary to optimize the effectiveness of the green street function. This study aims to identify and analyze the function of existing street trees according to the street tree planting criteria. The method used includes program development, site selection, and analysis to the conclusion. At the analysis stage, the identification results are described descriptively by reviewing the results of other similar studies. Meanwhile, the functional analysis is carried out based on the assessment of each identified tree species. The identification results showed that the number of trees planted was inadequate, but varied based on the types. The most common street tree function is visual quality, and the road that meets the most functional criteria is Jalan Ottista segment 2.